Analisis Pola Keausan Brake Shoe pada Kereta Mass Rapid Transit Jakarta - Vira Pramadhani Putri; Dahlan Dahlan; Totok Suryono (Fakultas Teknik Transportasi dan Logistik Trisakti, 2023)
Brake shoe is one of the components on train that has an important role in braking process, to perform braking brake shoe rubs against the wheel. Friction between the brake shoe and wheel continuously can cause wear on brake shoe. The purpose of this study is to determine the wear rate and service life of brake shoe and main cause of brake shoe wear faster. The research method used in this research is descriptive quantitative method. Based on the results of the study, at a distance of about 7000 km to 10000 km the brake shoe on trailer car experienced wear of about 4 mm to 8 mm while brake shoe on motor car was about 1 mm to 3 mm. The service life of brake shoe on trailer car when mileage reaches 40000 km to 50000 km while on the motor car it can reach 70000 km to 90000 km and the main cause of brake shoe wear is faster due to the large braking force generated due to the frequent braking of the train so that the friction on the brake shoe and the wheel is more frequent and can cause hot temperatures which make wear occur faster.